Organizational Culture as an Influencing Mediating Factor between the Transformational Leadership and Work Satisfaction: an Empirical Study on the Police Integrity in the Central Java Regional Police Command - Rycko Amelza Dahniel (Universitas Lampung, 2019)
The research investigates organisational structure as a mediating variable that influences the transformational leadership and the work satisfaction of police integrity in the areas under the jurisdiction of the Central Java Regional Police Command. Police integrity is an important phenomenon, as it is the foundation for realising trusted, modern, and professional police personnel, as expected by the Indonesian National Police (INP). The number of samples in this research was 200 police members from 10 working units in the Central Java Regional Police Command. The sampling method was purposively random sampling. The Structural Equation Model Analysis (SEM) was used to test the influence of the transformational leadership and work satisfaction by placing organisational culture as a mediating variable against police integrity. By the SEM analysis, this research found that police work satisfaction has influence over organizational culture (r= 0.49; p< 005), and the transformational leadership has significant influence over organizational culture (r= 0.37; p< 0.05). Organizational culture as a mediating variable has significant influence over police integrity (r= 0.26; p< 0.05). Furthermore, leadership has significant influence over police integrity (r= 0.39; p< 005), and work satisfaction has direct influence over police integrity (r= 0.24; p< 0.05). Therefore, it can be concluded that the transformational leadership and work satisfaction have strong indirect influence over organisational culture as a mediating variable against police integrity. Meanwhile, work satisfaction has weak direct influence (r=0.24; p<0.05) over police integrity.